PENGARUH STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BANK SULUTGO - Terok, Januar; Tumbel, Tinneke M.; Sumampouw, Harry (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Common stress is defined as the pressure, tension or unpleasant disturbance that comes from outside a person. The purpose of this study was to determine the effect of Job Stress on Employee Performance PT. Bank SulutGo.   Job stress is a condition in which there are one or several factors in the workplace that react with the worker so as to interfere with physiological conditions, and behavior. Job stress will arise when there is a gap between an individual's ability and the demands of his job. Stress is the gap between individual needs and the fulfillment of the environment. Samples taken as many as 60 respondents. Data collection methods used were questionnaires, interviews, and documentation. Data analyzed using descriptive research method of research is research that combine anatara qualitative method (descriptive) and quantitative.  In this research, the result of simple correlation shows the relationship or strong influence between stress and achivment variable equal to 0,667% and based on that calculation then sought contribution of variable stress and achievment the result is 44,89%. From result Regression analysis showed that the individual stressor factor has a positive relationship to the employee's work indicated by the variable coefficient where stress affects the decrease of employee achievement and from the calculation results obtained simple regression equation the relationship is positive. The conclusion of this research is to show that respondents are more likely to experience stress so that influence on employee performance, the higher the employee experiencing stress then the performance will decrease. So the authors suggest that companies need to pay attention to and maintain the stability of work stress caused by organizational factors include (physical and work factors, social factors, and organization) and individual factors for employee performance can be optimal so as not to affect employee performance.  Keywords: Stress On Job, Work Achievement